Little black book - Hurran, Nick; Livingston, Ron; Murphy, Brittany; Antoon, Jason (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
Stacy feels like her new boyfriend Derek may be the love of her life until she sneaks a peek at his palm pilot revealing listings for his former girlfriends.
Originally released as a motion picture in 2004.
Features: featurettes, trailers.
Ron Livingston, Brittany Murphy, Jason Antoon.
MPAA rating: PG-13.
DVD, Dolby digital 5.0 surround.
In English or French with optional French subtitles.
Keywords: Man-woman relationships -- Drama; Video recordings for hard of hearing people; Feature films; Comedy films; Romantic comedy films